High and low dose radiotherapy combined with ICIs for MSS colorectal cancer patients with liver metastases: a phase I study (HaRyPOT) - Ding, Yuxuan; Feng, Yong; Ye, Yangfan; Shen, Jiayi; Guo, Chang; He, Xia; Zhu, Liangjun; Wang, Lijun (Frontiers in Oncology, 2025)
IntroductionMicrosatellite stable (MSS) colorectal cancer with liver metastases (CLRM) responds poorly to immunotherapy, and various approaches to break immune tolerance have been tried. Radiotherapy in combination with immune checkpoint inhibitors is one of promising therapies, and the choice of radiotherapy and immunotherapy modalities is also a hot issue.MethodsHere, we report on a Phase I trial treating nine patients with MSS CLRM using a combination of high and low dose radiotherapy and immune checkpoint inhibitors (ICIs).ResultsThe primary endpoint of the trial was the safety and tolerability of this combination treatment modality. Secondary endpoints included the objective response rate (ORR), progression-free survival (PFS) and overall survival (OS). The study results showed that at three dose levels—single doses of 6Gy (n=3), 8Gy (n=3), and 10Gy (n=3)—the most common treatment-related adverse events (TRAEs) were nausea, vomiting, fatigue, and abnormal liver function. At the first condition assessment, four patients were observed to have stable disease (SD) and one patient achieved partial response (PR). In exploratory endpoint analyses, tissue biopsies and paired hematologic samples from patients showed M2 macrophage reduction. Plasma cytokines IL-10, IL-17, and INF-α increased after treatment with both drugs.DiscussionIn summary, this is the first clinical trial demonstrating the safety and immunogenic activity of combined high and low dose radiotherapy with ICIs in MSS colorectal cancer liver metastases (CRLMs). The combination therapy stimulated the immune response and altered the tumour microenvironment, warranting further exploration in the future.